Thermal Decomposition Kinetics Analysis and Its Application to Cigarette Flavouring of Methyl Cyclopentenolone Succinate Menthol Diester - Yu, Zhaojin; Wang, Haiyang; Li, Zhuo; Yan, Dingwei; Liang, Kewei; Yang, Xiaopeng; Qiu, Jianhua; Du, Fu; Ji, Xiaoming (Flavour and fragrance journal, 2025)
Methyl cyclopentenolone succinate menthol diester (compound 5) was synthesised from methyl cyclopentenolone, menthol and succinic anhydride using dicyclohexylcarbodiimide (DCC) and 4‐dimethylaminopyridine (DMAP) methods. The thermal decomposition process and kinetic behaviour of the compounds were studied at various heating rates (10°C, 20°C, 40°C, 60°C and 80°C min −1 ) using thermogravimetry‐derivative thermogravimetry (TG‐DTG), Kissinger‐Akahira‐Sunose (KAS) method, Flynn‐Wall‐Ozawa (FWO) method and Coats–Redfern method. The research revealed that TG curves approached the high‐temperature end with increasing heating rates, and the peak temperature of heat loss rate on the DTG curves tended to rise, but the magnitude of the change was smaller than that of heating rate. The apparent activation energy ( E a ) of thermal decomposition increased with the conversion rate. The E a of compound 5 ranged from 77.65 to 154.05 kJ mol −1 and from 82.56 to 156.43 kJ mol −1 calculated by KAS and FWO, respectively. The thermal decomposition process models of the compounds were found to be one‐dimensional diffusion models (D1). The results of the kinetic compensation effect showed that the fitting result of the KAS method was better than that of the FWO method. Pyrolysis results indicated the production of aromatic substances such as methyl cyclopentenolone, menthol and esters. Additionally, the results of cigarette flavouring showed that the smoking quality of cigarettes was improved by adding compound 5. In summary, the findings of this study not only offer insights into the thermal decomposition and development of slow‐release flavours under heated conditions, but also provide valuable references for assessing the thermal stability and utilisation potential of various substances, including biomass.